Study of Feminism and Women's Existence in the Novel Bumi Manusia by Pramoedya Ananta Toer - Yanuar Bagas Arwansyah; Nanda Saputra (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
Women are so close to idioms such as adversity, oppression, even to the "concept" that is already accepted by most people, that they are "objects" not "subjects" for men. Gender inequality is manifested in various forms of injustice that occur at various levels of society. This study aims to analyze the personality of the female characters, the gender injustice experienced by the female characters, and the value of character education contained in the novel Bumi Manusia by Pramoedya Ananta Toer. This study uses a qualitative descriptive technique. The object of this research is the meaning of the existence of women in the novel Bumi Manusia by Pramoedya Ananta Toer, a review of feminist literary criticism. The data in the research are in the form of dialogues, paragraphs, and narrations contained in the novel Bumi Manusia by Pramoedya Ananta Toer. Based on the results of the analysis and discussion, the data shows that the author describes several female characters who experience gender bias treatment, namely Nyai Ontosoroh, Annelies, Maiko, Min Hwa, and Sie-sie. The novel Bumi Manusia tends to use socialist feminism. Gender injustice experienced by female characters is the marginalization of women, subordination of women, stereotypes of women, violence against women, and double workload against women.